Agricultural impacts drive longitudinal variations of riverine water quality of the Aral Sea basin (Amu Darya and Syr Darya Rivers), Central Asia. (1st September 2021) - Leng, Peifang; Zhang, Qiuying; Li, Fadong; Kulmatov, Rashid; Wang, Guoqin; Qiao, Yunfeng; Wang, Jianqi; Peng, Yu; Tian, Chao; Zhu, Nong; Hirwa, Hubert; Khasanov, Sayidjakhon
Abstract: River ecosystems are under increasing stress in the background of global change and ever-growing anthropogenic impacts in Central Asia. However, available water quality data in this region are insufficient for a reliable assessment of the current status, which come as no surprise that the limited knowledge of regulating processes for further prediction of solute variations hinders the development of sustainable management strategies. Here, we analyzed a dataset of various water quality variables from two sampling campaigns in 2019 in the catchments of two major rivers in Central Asia—the Amu Darya and Syr Darya Rivers. Our results suggested high spatial heterogeneity of salinity and major ion components along the longitudinal directions in both river catchments, pointing to an increasing influence of human activities toward downstream areas. We linked the modeling outputs from the global nutrient model (IMAGE-GNM) to riverine nutrients to elucidate the effect of different natural and anthropogenic sources in dictating the longitudinal variations of the riverine nutrient concentrations (N and P). Diffuse nutrient loadings dominated the export flux into the rivers, whereas leaching and surface runoff constituted the major fractions for N and P, respectively. Discharge of agricultural irrigation water into the rivers was the major cause of the increases in nutrients and salinity. Given that the conditions in Central Asia are highly susceptible to climate change, our findings call for more efforts to establish holistic management of water quality. Graphical abstract: Image 1 Highlights: We provide the dataset in two Central Asian rivers addressing salinity and nutrients. Causal relationship between nutrient sources and concentrations was established. Longitudinal variations of nutrients and salinity were driven by irrigated croplands. N from leaching and P from surface runoff dominated in the export flux to the rivers.